UV-B Radiation as a Factor that Deserves Further Research in Bolivian Viticulture: A Review - Gutiérrez-Gamboa, G.; Pszczólkowski, p.; Cañón, P.; Taquichiri, M.; Peñarrieta, J. M. (South African Journal of Enology and Viticulture, 2021)
Bolivian viticulture has acquired an incipient notoriety in the international wine market due to the production of high-altitude wines with a high antioxidant potential. Andes agricultural regions present an advantage for wine production since UV-B radiation reaching the earth’s surface increases with altitude and varies with latitude, promoting the activation of plant defense mechanisms responsible for the synthesis of secondary metabolites. UV‐B radiation upregulates the biosynthesis of nitrogen, phenolic and volatile compounds that contribute to wine flavour. It is thought that the incident UV-B radiation in the Bolivian valleys makes it possible to obtain wines with high phenolic and aromatic potential, but the published results are not entirely conclusive. This manuscript addressed the geological and climatic features that affect Bolivian viticulture, and we reviewed the field studies carried out regarding the effects of altitude and UV-B radiation on flavour components of grapes and wines from Bolivian viticultural valleys. A high antioxidant capacity and trans-resveratrol content is found in grapes and wines from highaltitude Bolivian vineyards, including if they are compared to those samples from different wine countries. However, high UV-B radiation can result in bunch sunburn affecting some physico-chemical parameters of the produced wines. Scarce number of studies have been developed in this field despite this region present a valuable potential for research in order to quantify the effects of biologically damaging radiation on the synthesis of flavour components in grapes and some of them were not well scientifically controlled.